Antibacterial activity of certain spice extracts - Isa, Q Mandeel, A Hassan, Z (Journal of Spices and Aromatic Crops, 2003)
Seventeen raw spice samples were examined for phytochemical constihlents and antimicrobial properties. Qualitative phytochemical analysis of crude spice extracts revealed the occurrence of alkaloids, coumarins, flavonoids, saponins, terpenes and tannins. Turmeric, clove and bay leaf showed the highest frequency of occurrence of these plant components among others. Terpenes were present in 94.12% of the samples evaluated. Ethanol extracts of spice samples were in vitro evaluated for their antimicrobial properties using well diffusion assay against six Gram positive and Gram negative bacteria. Results showed that all the spice extracts, except black cardamom, possess biological activity on one or more of the test bacteria. Clove extracts displayed the highest antibacterial activity (19.5 mm) against Escherichia coli, followed by bay leaf (19 mm) against the same bacteria and cumin (19 mm) against Pseudomonas aeroginosa, at 1000 ug/100 ul. Extracts of galangale, turmeric and fennel also exhibited a broad spectrum biological activity. The most susceptible bacteria, based on frequency values, were E. coli (76.4%), P. aeruginosa and Bacillus subtilis (58.82%) and the least susceptible species were Salmonella arizonae (23.52%) and Enterobacter aerogenes (17.64%) at 1000 ug/100 ul. Overall, the presence of biologically active compounds and potent antimicrobial properties elucidate the potential use of spices in small amounts, individually or in combination in human therapy or folk medicine and as food preservative.